واقع المكتبة المدرسية ودورها في تكوين الوعي الثقافي للطلبة السوريين - مدارس اللاذقية نموذجاً- - عدوان سوسن; صالح حلا (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
تمتاز المكتبة المدرسية عن أنواع المكتبات الأخرى بكثرة عددها، وسعة انتشارها. فوجود مدرسة يتطلب إنشاء مكتبة فيها لتقدم خدماتها للطلاب والمعلمين على حد سواء. كما تمتاز بأنها أولى أنواع المكتبات التي يتعامل معها التلميذ, وستُبنى علاقته مستقبلاً بأنواع المكتبات الأخرى الموجودة في المجتمع اعتماداً على مدى تأثره بها، وانطباعه عنها، وبناءً على ما يكتسبه فيها من مهارات مكتبية في القراءة، والبحث، والحصول على المعلومات، وكل هذا لا يمكن أن يكون إلا باستحواذ المكتبة المدرسية على الشروط اللازمة كافة لنجاحها. فهل الشروط الأساسية لنجاح المكتبات متوافرة في مدارسنا الثانوية؟ هل بإمكان المكتبة المدرسية تحقيق الأهداف المرسومة لها؟ كيف يستطيع الطالب الاستفادة من المكتبة المدرسية؟ ما أهمية الدور الذي يمكن أن تقوم به لتحسين العملية التربوية وتطويرها ؟ ما التدابير التي يمكن اتخاذها لكي تحقق المكتبة المدرسية الأهداف التي وضعت من أجلها؟ The school library is distinguished from the rest of other types of libraries available in the community by advantages such as its great number and its capacity to spread. Where there’s a school, it is assumed that the library offers services to students and teachers alike. It is also characterized as the first type of library that the reader encounters in his life, and thus his relation to other types of libraries in the community will depend upon how much he is influenced by it and the impression it leaves and his acquisition of library skills such as reading, researching, and accessing information; hence appropriate conditions should be available to facilitate the success of school libraries. Are the basic conditions for the success of libraries available in our high schools? Can the school library achieve the goals set for it? How can the student benefit from the school library? How important is the role that can be done to improve and develop the educational process? What measures can be taken in order to achieve the school library goals set for it?